If (a–8)/3 = (a–3)/2 ,then find 'a'
14
7
–7
–21
Answers
Answered by
0
Answer:
by cross multiplication.
3a-9=2a-16
3a-2a=9-16
a=-7
Step-by-step explanation:
HOPE IT IS HELPFUL
MARK ME AS A BRAINLEAST
Answered by
2
Answer:
Ans: -7
Step-by-step explanation:
Please mark me as brainliest
Attachments:
![](https://hi-static.z-dn.net/files/d00/34707764ddef30ac15b91586b3043b8c.jpg)
Similar questions
Science,
2 months ago
Computer Science,
2 months ago
Math,
3 months ago
Computer Science,
11 months ago
Math,
11 months ago
Art,
11 months ago